Quality of life assessment in domestic dogs: An evidence-based rapid review. Issue 2 (November 2015) - Belshaw, Z.; Asher, L.; Harvey, N.D.; Dean, R.S.
Highlights: We provide a clear methodology for the assessment of validity, reliability and quality of life (QoL) instruments. Few authors of publications containing a QoL instrument define quality of life. Few of the instruments published for the assessment of QoL in dogs are validated. The quality of validated instruments for the assessment of QoL in dogs is variable. Abstract: Assessment of quality of life (QoL) is an important, increasingly popular outcome measure in veterinary research and practice, particularly in dogs. In humans, QoL is commonly assessed by self-reporting and since this is not possible for animals, it is crucial that instruments designed to measure QoL are tested for reliability and validity. Using a systematic, replicable literature search strategy, the aim of this study was to find published, peer-reviewed instruments for QoL assessment in dogs and to assess the quality of these. CAB Abstracts and PubMed were searched in July 2013 using terms relevant to dogs, wellbeing and QoL. Inclusion and exclusion criteria were applied. When instruments were not published in full, authors were contacted to obtain them. Criteria were applied to assess the quality, validity and reliability of the 52 instruments obtained. Twenty-seven additional instruments used in peer-reviewed publications were not included because they had not been fully described in the publication or were not provided by authors upon request. Most of the instruments reviewed (48/52) were disease-specific rather than generic. Only four publications provided a definition of QoL or wellbeing. Only 11/52 instruments demonstrated evidence of assessing reliability or validity, and the quality of these instruments was variable. Many novel, unvalidated instruments have been generated and applied as clinical outcomes before it was known whether they measured QoL. This rapid review can be used to identify currently available and validated canine QoL instruments, and to assess the validity and quality of new or existing instruments.